The Trade, Trapping, and Utilization of Lorises in India - Ahmed, Abrar (Journal of the Bombay Natural History Society (JBNHS), 2013)
Slow Loris Nycticebus bengalensis and Slender Loris Loris lyddekerianus are much favoured species in the illegal live mammal trade. Lorises are small sized furry primates, having large round eyes. They are easy to keep due to their omnivorous diet and a solitary lifestyle. Lorises rank high on the cute-and-cuddly scale and are much sought after as pets worldwide. This paper discusses the more or less covert trade, trapping and organised wildlife trafficking, and utilisation of lorises in India.